Analisis Efektivitas Penggunaan E-Filing Bagi Wajib Pajak Pribadi dalam Pelaporan PPh Pasal 21 pada Karyawan PT Tirta Mahakam - Andi Indrawati3, Cindi Afriyani1, Titin Ruliana2 (EKONOMIA, 2021)
The purpose of this research is to know and analyze the effectiveness of the use of e-filing for personal taxpayers in reporting Pph article 21 to employees of PT. Tirta Mahakam. In accordance with the objectives of this study, the subject matter put forward